Senolytics: A Translational Bridge Between Cellular Senescence and Organismal Aging - Thoppil, Harikrishnan; Riabowol, Karl (Frontiers in Cell and Developmental Biology, 2020)
Ageing is defined as a progressive decrease in physiological function accompanied by a steady increase in mortality. The antagonistic pleiotropy theory proposes that ageing is largely due to the natural selection of genes and pathways that increase fitness and decrease mortality early in life but contribute to deleterious effects & pathologies later in life. Cellular Senescence is one such mechanism, which results in a permanent cell cycle arrest that has been described as a mechanism to limit cancer cell growth. However, recent studies have also suggested a dark side of senescence in which a build-up of senescent cells with age leads to increased inflammation due to a senescence associated secretory phenotype (SASP). This phenotype that includes many cytokines promotes tumorigenesis and can exhaust the pool of immune cells in the body. Studies clearing senescent cells from mice using the p16-based transgene INK-ATTAC have shown that senescent cells can impact both organismal ageing and lifespan. Here we discuss these advances that have resulted in the development of a whole new class of compounds known as senolytics, some of which are currently undergoing clinical trials in humans for treating a variety of age-related pathologies such as osteoarthritis.